Influence of the structure of some types of fillers introduced to the yogurt recipe on changes in its rheological indicators - Samilyk, Maryna; Helikh, Anna; Ryzhkova, Taisia; Bolgova, Natalia; Nazarenko, Yuliya (Eastern-European Journal of Enterprise Technologies, 2020)
The data set is obtained regarding changes in viscosity, water-holding capacity, active and titrated acidity of yogurts using natural fillers. The possibility of using vegetable fillers with different types of structure (powder, solid and pasty) in the technology of yogurt is analyzed. The studies are relevant in view of improving the quality of yogurts and giving them the status of natural ones due to removing stabilizers, flavors and aromatic additives from their composition. In addition, the introduction fillers into the recipe of yogurts, as a rule, leads to a deterioration of their rheological parameters: a decrease in viscosity, separation of whey and deterioration of the taste properties of the product. This causes an increase in the amount of flavors and stabilizers introduced into their composition, which negatively affects the population of “living microflora” and the biological value of the product. It is found that all the fillers (strawberry powder, candied beets and strawberry jam) had no negative effect on the fermentation process. The influence of dietary fibers that are part of fillers (candied beets, strawberry powder and strawberry jam) on the rheological properties of the product is investigated. Changes in viscosity, water-holding capacity, active and titrated acidity of yogurts with different types of fillers were determined and analyzed immediately after production and during storage. The positive effect of pectin-containing fillers on the hydrophilic properties of yogurts, which increase the water-holding capacity of the product by 2–3 %, is experimentally shown. Based on the data obtained, the feasibility of using the proposed types of fillers, namely strawberry powder and candied beets, in yogurt production without the use of stabilizers, flavors and other food additives is proved. Storage capacity is found, yogurts are developed and shelf life specified in the regulatory documents is determined